Soichi : Junji Ito story collection - Itō, Junji, 1963- (Viz signature., 2023)
"Soichi, the unhinged second son of the Tsujii family, chews nails and makes them clatter and clack as he spouts horrific curses to bring about the most bizarre happenings. Whether it's summer holidays or a birthday party, Soichi can turn any occasion into a nightmare in a heartbeat. What is the terrible secret of his origin?' Meanwhile, tormented by his little brother's never-ending pranks, older brother Koichi has a soundproof room built. But why does it have a series of four doors? And then there's the strange phenomenon surrounding the handmade casket their grandfather left behind. What on earth--or hell--has the family seen there? Ten tales that celebrate the sinister and hilarious world of Junji Ito's favorite antihero, Soichi!"--